2017
DOI: 10.7717/peerj.4033
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of perioperative stress in colorectal cancer by use of in vitro cell models: a systematic review

Abstract: BackgroundThe perioperative period is important for patient outcome. Colorectal cancer surgery can lead to metastatic disease due to release of disseminated tumor cells and the induction of surgical stress response. To explore the overall effects on surgically-induced changes in serum composition, in vitro model systems are useful.MethodsA systematic search in PubMed and EMBASE was performed to identify studies describing in vitro models used to investigate cancer cell growth/proliferation, cell migration, cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Studies focusing on colorectal carcinoma have indicated that stress-inducing factors, such as autoimmune dysfunction, surgical wounds, anesthesia, and postoperative pain, can inhibit cellular immune functions in patients with malignant tumors and thereby promote tumor extension and metastasis. [3032] Thus, reducing the stress response by optimizing the intraoperative and postoperative management of patients with EC could potentially improve outcomes. Factors likely to contribute to the stress response in patients with EC undergoing open thoracotomy include relatively large surgical wounds and substantial postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Studies focusing on colorectal carcinoma have indicated that stress-inducing factors, such as autoimmune dysfunction, surgical wounds, anesthesia, and postoperative pain, can inhibit cellular immune functions in patients with malignant tumors and thereby promote tumor extension and metastasis. [3032] Thus, reducing the stress response by optimizing the intraoperative and postoperative management of patients with EC could potentially improve outcomes. Factors likely to contribute to the stress response in patients with EC undergoing open thoracotomy include relatively large surgical wounds and substantial postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…For patients undergoing cancer surgery, the risk for cancer dissemination and metastasis is supposed to be enhanced during the perioperative period (1,2). Cancer cells are released into the circulation due to traumatization of tumor vessels and surgical manipulation of the tumor tissue (3).…”
mentioning
confidence: 99%
“…Five reviews (17,24,34,44,46) indicated that the following tools were used without any reported adaptations by review authors: Cochrane risk of bias (55); Quality Assessment of Diagnostic Accuracy Studies (QUADAS-2) (59); ToxRTool (61); STROBE (65); Grading of Recommendations, Assessment, Development and Evaluations (GRADE) (58) respectively. Authors of three reviews (20,32,39) adapted or modified validated criteria for use with in vitro studies. These included GRADE (adapted for in vitro) (58); Newcastle-Ottawa quality assessment (adapted) (60), modified Research Triangle Institute (RTI) Item Bank for cross-sectional studies (64).…”
Section: Resultsmentioning
confidence: 99%